Investigating the Relationship between Test-Taking Anxiety and Test-Takers’ Performance on the IELTS Test - Dang Arif Hartono (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Although there is a growing body of research indicating that anxiety relates to foreign language learning, the correlation between anxiety and learners’ performance on a high-stakes testing context has not been fully explored. To date, studies investigating the relationship between test-taking anxiety and test-takers’ performance are not only limited in number, but also partial in nature as most of them only looked at one aspect of test-takers performance, i.e. listening, speaking, or writing performance only. This study is aimed at investigating the relationship between test-taking anxiety and test-takers’ performance with a holistic view, taking into account the test-takers’ performance on the listening, reading, speaking, and writing modules of the International English Language Testing System (IELTS™) test. The participants in this study were 15 government officials taking an IELTS test preparation program. Two instruments were utilized in this study: (1) a set of test-taking anxiety questionnaire items to measure the level of anxiety and, (2) the official IELTS™ test to measure test-takers’ performance. The results indicated that there was a weak to moderate correlation between test-taking anxiety and the test-takers’ performance across different modules of the IELTS test. These results corroborate the findings from previous studies.